Beyond Numbers: Unravelling the Dimensions of Environmental Accounting through Bibliometric Exploration - Edy Susanto; Khoiruddin (The Es Accounting And Finance, 2023)
Environmental accounting has received significant attention in recent years due to the increasing awareness of the impact of business activities on the environment. Traditional accounting practices often need to capture the true costs of environmental externalities, necessitating a more comprehensive approach. This study aims to explore the dimensions of environmental accounting beyond numbers by using an exploratory bibliometric methodology. By conducting a systematic review of the relevant literature and analyzing bibliometric data, this research seeks to identify emerging trends, key contributors, and research gaps in the field of environmental accounting.